Variations in Antibiotic Susceptibility Profile of Staphylococcus aureus after Povidone-Iodine Stress - Iraj Nikokar, Hadi Sedigh Ebrahim-Saraie, Haleh Ganjian (Tabriz University of Medical Sciences, 2017)
Background: Staphylococcus aureus is one of the major causes of nosocomial infection which is the most commonly identified agent responsible for skin and soft tissue infections. Cleaning of the skin before an intervention remarkably reduces the risk of infections. The aim of this study was to investigate the effects of povidone-iodine stress on the antimicrobial susceptibility pattern of S. aureus resistant subpopulation. Methods: A 24 h fresh culture was prepared by S. aureus inoculation into the tube containing trypticase soy broth (TSB). Then an povidone-iodine resistant subpopulation of strain was selected by exposure to povidone-iodine stress with concentrations 3% and 10% (wt/vol). The resulting survived cells were maintained in 10 mL TSB. The Antibiotic susceptibility testing was performed on strains by disk diffusion method according to CLSI recommendations. Results: Evaluation of antimicrobial susceptibility pattern revealed significant differences in zone of inhibitions between stressed and unstressed strains. S. aureus strains stressed at 3% povidone-iodine concentrations showed statistically smaller zone of inhibition against clindamycin, methicillin and chloramphenicol compared to unstressed strains. Although, 3% povidone-iodine stressed strains were become more susceptible to penicillin G and cephalothin. Rifampicin, ciprofloxacin, methicillin and chloramphenicol in stressed strains showed a significant decrease in zone of inhibition at 10% povidone-iodine concentrations, and higher sensitivity to co-trimoxazole, cephalothin and cephalexin. Conclusion: The observed changes in antimicrobial susceptibility patterns of S. aureus strains can contribute to povidone-iodine stresses. Although extend study on wider range of skin and wound associated pathogens necessitate to reach a comprehensive conclusion.